Pengembangan Media Kotak Berhitung Penjumlahan dan Pengurangan - Sandy Aulia; Asep Sukenda Egok; Fitria Lestari (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This research aims to develop a product in the form of Addition and Subtraction Counting Box Media Development in Grade I Mathematics Learning at SD Negeri Nawangsasi which is valid, practical and effective for use in learning. This research is a development research with four-D development model. Data collection techniques used interviews, observations, questionnaires and tests. Based on the results of the assessment analysis by the three validity experts with an average score of 0.81, it shows that the Addition and Subtraction Counting Box Media in Mathematics Learning meets very valid criteria. While the results of the teacher and student practicality sheet research obtained an average score of 81% that the Addition and Subtraction Counting Box Media in Mathematics Learning practical criteria. And the results of the effectiveness research of all first grade students obtained that the Addition and Subtraction Counting Box Media in Mathematics Learning meets the High criteria with a final score of 0.72 so that it can be concluded that the Addition and Subtraction Counting Box Media in Mathematics Learning meets the valid, practical and effective criteria, and is suitable for use in learning. Keywords: Counting Box, Mathematics, Addition, Subtraction.